KONSEP WASIAT PERSPEKTIF HADIST DAN KOMPILASI HUKUM ISLAM - Triandiki, Dimas; Afif, Faisal (MASILE, 2024)
This research aims to analyze the concept of will in a hadith perspective and how its application correlates with Islamic family law. The will is one of the important aspects of Islamic law that plays a significant role in maintaining justice and the well-being of the family and the Muslim community. Through a literature review of authentic hadiths, this research explores the meaning, principles, and requirements of wills, as well as their implications in the context of family relationships i.e. the concept of wills in hadiths, covers theoretical and ethical understanding of how the Prophet Muhammad SAW directed his people in giving wills, including the values of wisdom and morality contained in them, i.e. Islamic family law, discusses how wills affect the division of property, relationships between siblings, guardianship, and responsibilities between family members. Key words: Law, Will, and Hadith